2022
DOI: 10.1002/bab.2308
|View full text |Cite
|
Sign up to set email alerts
|

Development of a recombinant nucleocapsid protein‐based ELISA for the detection of IgM and IgG antibodies to SARS‐CoV‐2

Abstract: Coronavirus 2019 (COVID-19) is a global concern for public health. Thus, early and accurate diagnosis is a critical step in management of this infectious disease. Currently, RT-PCR is routine diagnosis test for COVID-19, but it has some limitations and false negative results. enzyme-linked immunosorbent assay (ELISA) against SARS-CoV-2 antigens seems to be an appropriate approach for serodiagnosis of COVID-19. In the current study, an ELISA system, using a recombinant nucleocapsid (N) protein, was developed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Enzyme-linked immunosorbent assay (ELISA) is often used for the detection of viral antibodies and has been developed as a rapid diagnostic test kit due to its ease of operation and use of inexpensive equipment. In ELISA of SARS-CoV-2, different structural proteins could be used as Ag to detect the corresponding antibodies and researchers have developed ELISAs with good sensitivity and specificity [ 83 86 ]. Using microfluidic technology, González-González et al [ 87 ] developed an automated ELISA chip for detecting antibodies to SARS-CoV-2, enabling on-site testing that may only require a smartphone with a camera.…”
Section: Rapid Detection Methodsmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA) is often used for the detection of viral antibodies and has been developed as a rapid diagnostic test kit due to its ease of operation and use of inexpensive equipment. In ELISA of SARS-CoV-2, different structural proteins could be used as Ag to detect the corresponding antibodies and researchers have developed ELISAs with good sensitivity and specificity [ 83 86 ]. Using microfluidic technology, González-González et al [ 87 ] developed an automated ELISA chip for detecting antibodies to SARS-CoV-2, enabling on-site testing that may only require a smartphone with a camera.…”
Section: Rapid Detection Methodsmentioning
confidence: 99%
“…The recombinant construct (pET23a-SsIR-Ss1a) was transformed into competent E . coli DH5α cells (Novagen, USA), using the heat shock technique [ 28 ]. The related SsIR-Ss1a was sequenced (S1, Sequence of the cloned antigen (rSsIR-Ss1a)) and used to verify the cloning accuracy of the plasmid isolated from transformants (GenScript, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant Ncap protein has also been used to facilitate development of both ELISA [9][10][11][12] and lateral flow diagnostics systems [12] [13] [14,15]. The SARS-CoV-2 Ncap protein has been suggested as a possible vaccine candidate [16,17] and it has been demonstrated that immunization with recombinant Ncap produced in Escherichia coli induced an antibody response in the lungs of rats [18].…”
Section: Introductionmentioning
confidence: 99%